2023
DOI: 10.1029/2022gl102394
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Scattering of Radiation Belt Electrons at Saturn by Ion Cyclotron Waves

Abstract: By constructing an empirical model of the spectral and latitudinal distribution of ion cyclotron waves on the basis of Cassini datasets, we investigate the resonant interactions between ion cyclotron waves and radiation belt electrons at Saturn. Calculations based on quasi‐linear bounce‐averaged diffusion coefficients show that at Saturn ion cyclotron waves can efficiently pitch angle scatter >∼1 MeV to tens of MeV electrons into the loss cone thereby inducing precipitation loss, while the mixed and momentum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Besides ECH waves, other wave modes including whistler‐mode chorus waves (Menietti et al., 2013), hiss waves (Menietti et al., 2019; Woodfield et al., 2022), Z‐mode waves (Menietti et al., 2016; Wu et al., 2021; Ye et al., 2009, 2010), and ion cyclotron waves (e.g., Leisner et al., 2005, 2006, 2011; Long et al., 2022; Russell et al., 2006) are also frequently observed in Saturn's magnetosphere. These plasma waves are recognized to significantly impact the local acceleration and loss processes of Saturn's radiation belt electrons by wave‐particle interactions (e.g., Cao et al., 2023; Gu et al., 2013; Kollmann et al., 2018; Menietti et al., 2012; Woodfield et al., 2018, 2019, 2022; Yu et al., 2019). It is also reported that ECH waves could interact with electrons in the energy range from ∼10 eV to several keV, leading to the generation of diffuse aurora (Tripathi et al., 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Besides ECH waves, other wave modes including whistler‐mode chorus waves (Menietti et al., 2013), hiss waves (Menietti et al., 2019; Woodfield et al., 2022), Z‐mode waves (Menietti et al., 2016; Wu et al., 2021; Ye et al., 2009, 2010), and ion cyclotron waves (e.g., Leisner et al., 2005, 2006, 2011; Long et al., 2022; Russell et al., 2006) are also frequently observed in Saturn's magnetosphere. These plasma waves are recognized to significantly impact the local acceleration and loss processes of Saturn's radiation belt electrons by wave‐particle interactions (e.g., Cao et al., 2023; Gu et al., 2013; Kollmann et al., 2018; Menietti et al., 2012; Woodfield et al., 2018, 2019, 2022; Yu et al., 2019). It is also reported that ECH waves could interact with electrons in the energy range from ∼10 eV to several keV, leading to the generation of diffuse aurora (Tripathi et al., 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The present study employs the quasi‐linear diffusion coefficient calculation procedure as described in Yao et al. (2023). The procedure generalizes the diffusion coefficient formula in Glauert and Horne (2005) to directly take numerical solutions of a general wave dispersion relation.…”
Section: Methodsmentioning
confidence: 99%
“…Quasi-linear diffusion theory (Kennel & Engelmann, 1966) is used to quantify the resonant interactions between EMIC waves and ring current protons. In the present study, we use the Full Diffusion Code (FDC) (e.g., Cao et al, 2016Cao et al, , 2017aCao et al, , 2019Cao et al, , 2023Ni et al, 2015Ni et al, , 2018 to calculate the bounce-averaged pitch angle scattering rates of ring current protons due to interactions with oblique propagating EMIC waves in a multi-ion plasma for a nondipolar background magnetic field. The total plasma density, which is assumed to be constant along the entire magnetic field line, is adopted from the plasma trough density model of Sheeley et al (2001).…”
Section: Methods Descriptionmentioning
confidence: 99%